Jolaye oasis (Abunjem) as a connecting place between Fezzan district and the cities of the Libyan western coast during the Roman era (Journal of Human Sciences, 2021)
JOLAYE (AbuNjem) oasis is one of the oldest  human  settlements in Libya since the prehistoric era , stone tools were found it dated the ancient stone era and the modern stone era. JOLAYE oasis is located on boarders of Fizzan district in the north and  locates in the middle zone in the southern sides in the desert  area in the middle of Libya in the depression of  Wadi Bai Elkhaeb , this strategic important location made it as a connetion between Fizzan and the western coast of Libya since the ancient era and is considered a suitable place for the rest of the commercial caravans  and travellers. And the Roman campaign that entered JERMA the capital of Fizzan has started from it, as result of the importance of the strategic location of the oasis on the road of the desert caravans going to Fizzan. This district  has an important  role in the age of Romans as it is one of the boarded  positions on the desert as they stayed in  it on 201 AD by building a fortress  in  this  location that was called JOLAY and it is one of the mos t important  fortress that were established on of the sides of the desert during the Roman era.